Prenatal substance exposure and infant neurodevelopment: a review of magnetic resonance imaging studies - Leela Shah; Leela Shah; Christy D. Yoon; Alessandra M. LaJeunesse; Lilly G. Schirmer; Emma W. Rapallini; Elizabeth M. Planalp; Douglas C. Dean; Douglas C. Dean; Douglas C. Dean (Frontiers in Human Neuroscience)
Amid the ongoing global substance use crisis, prenatal health research has increasingly focused on the impact of both licit and illicit substance use on fetal development, and in particular brain development. Magnetic resonance imaging (MRI) has become a critical non-invasive tool for investigating how such exposures influence the developing brain. In this review, we summarize findings from 25 peer-reviewed studies that leverage structural, functional, and diffusion MRI to examine the effects of prenatal exposure to alcohol, opioids, methamphetamines, cocaine, nicotine, or cannabis. Particular attention was given to studies that paired infant MRI data with developmental outcomes. Existing research has implicated cortical and sub-cortical gray and white matter regions across substance exposures, with associations between MRI findings and developmental outcomes in infancy. We identify key limitations in the existing literature, including small sample sizes, lack of control for prematurity, sex, co-occurring exposures, limited developmental assessment, and insufficient longitudinal follow-up. We highlight the need for future research linking early neuroimaging findings to developmental outcomes, particularly in large, diverse, and nationally representative cohorts. Such work is essential for informing evidence-based policies, clinical guidelines, and targeted interventions for families impacted by prenatal substance exposure.